Entrelaçamento da história de vida com os processos formativos de uma professora de escola no campo do município de Restinga Sêca/RS - Bolzan, Mariane (2016)
This research of Master of Education, linked to the research theme ''Formation, knowledge and professional development'' (LP1), of the Pos Graduation Program in Education of the Universidade Federal de Santa Maria (PPGE/UFSM), arises from the interest about how the life history of an alphabetizer teacher, that works in a rural school, in Restinga Seca (RS) city, is related to its formative process as teacher. Through this study, aims to do an approximation of the alphabetizer teacher to the memories of her personal and professional trajectory, remembering steps of her formation process. The research is qualitative, according to Bogdan and Biklen (1994) studies, using the life history methodology, being the productions through scheduled meetings with the contributor. The instruments that were part in the information collecting were the interview semi structured, oral and written, the registers in field diary and the autobiographical reports also oral and written, all of them recorded, transcripted and organized according to the following analysis categories: school memories, initial formation, and teaching practice. Among the authors used as theoric contribuition in this work, are Abrahão (2006, 2008), Antunes (2007, 2010, 2014), Arroyo (2000), Bosi (1994), Caldart (2000), Farias (2015), Freire (2011), Josso (2000, 2006), Meurer (2010), Nóvoa (1988), Passeggi (2006), Tardif (2010) and Souza (2006), that collaborated to the studies about teachers formation, life history and rural education. Concluding this work, it was possible to give visibility and possibilities to the teacher, that acts in countryside, revisit her formation processes and also possibilities to feel valued by the work she does. This valorization of her knowledge contributed to the teacher believes in the transformation potential of the countryside school where she works.